Antibacterial Activity of Ethanol Extract of Porang Tubers (Amorphophallus muelleri Blume) Against the Growth of Helicobacter pylori ATCC 43504, Shigella dysenteriae ATCC 13313 and Vibrio Cholerae ATCC 14035 Bacteria - Nuryanti, Siska; Nurung, Ayyub Harly; Putra, Aryadi Surya (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Porang tubers (Amorphophallus muelleri Blume) are known as local plants that contain active compounds such as glucomannan, saponins and flavonoids, which are thought to act as antibacterials. This study was conducted to determine the extent of the ability of ethanol extract of porang tubers to inhibit and kill Helicobacter pylori ATCC 43504, Shigella dysenteriae ATCC 13313, and Vibrio cholerae ATCC 14035 bacteria, by looking at the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values. The extract was made using the maceration method using 96% ethanol, then tested for antibacterial properties using the liquid dilution method for MIC and the drop plate method for MBC. The results showed the MIC value for the three test bacteria at a concentration of 50,000 ppm. Meanwhile, the MBC value was not achieved even at the highest concentration, which was 100,000 ppm. Based on the results of this study, it can be concluded that the antibacterial effectiveness of ethanol extract of porang tubers is still relatively weak on Helicobacter pylori ATCC 43504, Shigella dysenteriae ATCC 13313, and Vibrio cholerae ATCC 14035 bacteria.